2016
DOI: 10.1007/s00192-016-2956-1
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injuries after episiotomy: systematic review and meta-analysis

Abstract: IntroductionThere is conflicting evidence on whether mediolateral episiotomy (MLE) reduces the risk of obstetric anal sphincter injuries (OASI) in spontaneous vaginal deliveries (SVD).ObjectivesA systematic review was undertaken to compare rates of OASI amongst women who had undergone mediolateral episiotomy versus those who did not.MethodsᅟSearch strategyElectronic searches were performed in literature databases: CINAHL, Cochrane, EMBASE, Medline and MIDIRS from database inception to July 2015. Studies were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 35 publications
5
36
2
5
Order By: Relevance
“…Notably, the reduction in OASI rate observed in the study cohort was not associated with a change in episiotomy rates, as described for other interventions . Previous studies have indicated that episiotomy may be protective against OASI, and that the angle of the episiotomy cut affects outcomes . The OASI care bundle, which has been launched by the UK Royal College of Obstetricians and Gynaecologists, includes optimization of the angle of episiotomy as one of its components.…”
Section: Discussionmentioning
confidence: 57%
“…Notably, the reduction in OASI rate observed in the study cohort was not associated with a change in episiotomy rates, as described for other interventions . Previous studies have indicated that episiotomy may be protective against OASI, and that the angle of the episiotomy cut affects outcomes . The OASI care bundle, which has been launched by the UK Royal College of Obstetricians and Gynaecologists, includes optimization of the angle of episiotomy as one of its components.…”
Section: Discussionmentioning
confidence: 57%
“…A recent meta-analysis of observational data concluded that mediolateral episiotomy may reduce OASIS and should not be withheld, especially in nulliparous women. 12 In fact, after adjusting for confounding factors, mediolateral episiotomy has shown a significant 2.5 times reduction in developing lacerations in primiparous women compared with no episiotomy. 8 However, other studies have shown that episiotomy and 3rd or 4th degree perineal lacerations increase the risk of anal incontinence after vaginal birth by 1.7 and 2.7 times, respectively.…”
mentioning
confidence: 97%
“…The effect of mediolateral episiotomy on obstetric anal sphincter injuries (OASIS) in spontaneous vaginal deliveries is not completely clear. A recent meta‐analysis of observational data concluded that mediolateral episiotomy may reduce OASIS and should not be withheld, especially in nulliparous women . In fact, after adjusting for confounding factors, mediolateral episiotomy has shown a significant 2.5 times reduction in developing lacerations in primiparous women compared with no episiotomy .…”
mentioning
confidence: 99%
See 2 more Smart Citations